Prostaglandin D2 synthase modulates macrophage activity and accumulation in injured peripheral nerves. Issue 1 (3rd September 2019) - Forese, Maria Grazia; Pellegatta, Marta; Canevazzi, Paolo; Gullotta, Giorgia S.; Podini, Paola; Rivellini, Cristina; Previtali, Stefano C.; Bacigaluppi, Marco; Quattrini, Angelo; Taveggia, Carla
Abstract: We have previously reported that prostaglandin D2 Synthase (L‐PGDS) participates in peripheral nervous system (PNS) myelination during development. We now describe the role of L‐PGDS in the resolution of PNS injury, similarly to other members of the prostaglandin synthase family, which are important for Wallerian degeneration (WD) and axonal regeneration. Our analyses show that L‐PGDS expression is modulated after injury in both sciatic nerves and dorsal root ganglia neurons, indicating that it might play a role in the WD process. Accordingly, our data reveals that L‐PGDS regulates macrophages phagocytic activity through a non‐cell autonomous mechanism, allowing myelin debris clearance and favoring axonal regeneration and remyelination. In addition, L‐PGDS also appear to control macrophages accumulation in injured nerves, possibly by regulating the blood–nerve barrier permeability and SOX2 expression levels in Schwann cells. Collectively, our results suggest that L‐PGDS has multiple functions during nerve regeneration and remyelination. Based on the results of this study, we posit that L‐PGDS acts as an anti‐inflammatory agent in the late phases of WD, and cooperates in the resolution of the inflammatory response. Thus, pharmacological activation of the L‐PGDS pathway might prove beneficial in resolving peripheral nerve injury. Main Points: L‐PGDS supports nerve regeneration after injury. L‐PGDS regulates macrophages phagocytosis and accumulation in a non‐cell autonomous way. L‐PGDS controls Blood‐Nerve Barrier permeability and SOX‐2 expression in Schwann cells.